Income redistribution and access to innovations in health care - María del Carmen García-Alonso; Owen O'Donnell (University of Kent, Department of Economics, 2001)
We study the impact a redistribution of income has on the decisions of a health care innovator and the utility of consumers. We find that income redistribution from rich to poor increases the quality of the medical innovation, reduces its price and increases the utility of some of the consumers whose income is reduced through the redistribution.
Keywords: D4; L1; I1; 330; Health care; Innovation; Income Redistribution; Gesundheitsversorgung; Medizin; Innovation; Einkommensumverteilung; Konsumentenverhalten; Theorie